2007
DOI: 10.1002/ejic.200600889
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐ and Intermolecular H···Cl–Ni Bonding Patterns in a Series of Highly Preorganized Dinuclear Nickel(II) Complexes

Abstract: Four dinickel complexes [L1Ni2(μ‐Cl)(Cl)2]·2CH3OH (1a), [L1Ni2(μ‐Cl)(CH3OH)](ClO4)2 (1b), [L2Ni2(μ‐Cl)Cl2(H2O)2]·H2O (2) and [L3Ni2Cl2(CH3OH)2]Cl·2CH3OH (3) were synthesized and structurally characterized. The ligand scaffolds have a central pyrazolato bridge and N‐donor chelate arms that provide two proximate binding pockets for the nickel ions. While the longer ligand side arms in 1a, 1b and 2 induce Ni···Ni distances of around 4.0 Å and favour incorporation of a chlorido bridge within the dimetallic pocket,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…There are eight structurally characterized dinuclear octahedral nickel(II) complexes of bis-tetradentate pyrazolate -based ligands in the literature. As expected, the Ni–N pyrazolate bonds are slightly shorter, due to the negatively charged nature of the pyrazolate ring, 1.943(4)–2.144(3) Å, than the Ni–N triazole bonds in the triazole complexes reported in this work, 2.040(3)–2.119(4) Å (Table ). The Ni–N amine and Ni–N py bonds in the pyrazolate complexes (2.096(3)–2.205(1) and 2.043(3)–2.178(5) Å, respectively) are similar or slightly longer than in our triazole complexes (2.093(3)–2.132(4) and 2.039(4)–2.082(3) Å, respectively, Table ).…”
Section: Resultssupporting
confidence: 72%
“…There are eight structurally characterized dinuclear octahedral nickel(II) complexes of bis-tetradentate pyrazolate -based ligands in the literature. As expected, the Ni–N pyrazolate bonds are slightly shorter, due to the negatively charged nature of the pyrazolate ring, 1.943(4)–2.144(3) Å, than the Ni–N triazole bonds in the triazole complexes reported in this work, 2.040(3)–2.119(4) Å (Table ). The Ni–N amine and Ni–N py bonds in the pyrazolate complexes (2.096(3)–2.205(1) and 2.043(3)–2.178(5) Å, respectively) are similar or slightly longer than in our triazole complexes (2.093(3)–2.132(4) and 2.039(4)–2.082(3) Å, respectively, Table ).…”
Section: Resultssupporting
confidence: 72%
“…The chlorido-aqua coordination motif can thus be considered as a dynamic bridging unit. This process likely goes via dissociation of the water molecule and possibly via a chlorido bridged intermediate, followed by reinsertion of water. Exchange of H 2 O in related (H)­O···H–O­(H) bridging units was previously shown to proceed rapidly …”
Section: Resultsmentioning
confidence: 99%
“…Meyer and co-workers have shown that ligand (L 1 )is capable of producing dinuclear systems in which the metal ions [copper(II), 10 zinc(II), 11 nickel(II) 12 ] are singly-bridged by the central pyrazolate moiety and coordinated to the tertiary amine and the two pyridine donors of the pendant arms, with the two last positions occupied by solvent or anion molecules. This is exactly the binding mode we wish to see adopted, but for iron(II), and preferably with the last two positions occupied by coordinating anions that are known to help confer SCO-activity on the iron centres, such as NCS and NCSe.…”
Section: Introductionmentioning
confidence: 99%